Sudden Cardiac Death—A New Insight Into Potentially Fatal Genetic Markers - Primorac, Dragan; Odak, Ljubica; Perić, Vitorio; Ćatić, Jasmina; Šikić, Jozica; Radeljić, Vjekoslav; Manola, Šime; Nussbaum, Robert; Vatta, Matteo; Aradhya, Swaroop; Sofrenović, Tanja; Matišić, Vid; et al. (Frontiers in Medicine, 2021)
Sudden cardiac death (SCD) is an unexpected and dramatic event. It draws special attention especially in young, seemingly healthy athletes. Our scientific paper is based on the death of a young, 23-year-old professional footballer, who died on the football field after a two-year history of cardiac symptoms. In this study we analyzed clinical, ECG and laboratory data, as well as results of genetic testing analysis in family members. To elucidate potential genetic etiology of SCD in this family, our analysis included 294 genes related to various cardiac conditions.